DESIGNING ANDROID-BASED MOBILE NOTIFICATION APPLICATION TO SUPPORT THE PERFORMANCE OF EMPLOYEES IN TANGGAMUS REGENCY GOVERNMENT - Ricco Herdiyan Saputra; Afrizal Martin; Yuniatun Yuniatun (SRA Publishing, 2021)
Communication plays an important role in uniting various activities in life, the process of information and between individuals as well as between people so that interaction occurs between them. Communication in the present, occurs both directly and using communication media. The government supports the development of current technology and expects a system that helps all employees work in government agencies. In this study, applications will be made that are expected to help and support them. This application is used to send real time information notifications, receive, take action, and send notifications to desired employees and also real time. Information sent in the form of announcements of events, meetings, and other activities while discussing, and discussion will be made for employees of their work in the report to fill in the appropriate tasks and for employees who have more work. In addition, this application uses Google Cloud Messaging (GCM) to send information and conversation notifications. So that, information that is announced and translated is sent at a time that can be accessed easily, an application created on an Android-based mobile device with information and changes sent are made by a Web servicebased application as server application, so notifications and transfer information will be sent as soon as there is an internet connection. Based on the assistance, this application will be run as soon as possible to help the Tanggamus Regency Secretariat office.